Digital media and innovation : management and design strategies in communication - Gershon, Richard A. (Los Angeles : SAGE, 2017)
Digital Media and Innovation takes an in-depth look at how smart, creative companies have transformed the business of media and telecommunications by introducing unique and original products and services. Today's media managers are faced with the same basic question: what are the best methods for staying competitive over time? In one word: innovation. From electronic commerce (Amazon, Google) to music and video streaming (Apple, Pandora, and Netflix), digital media has transformed the business of retail selling and personal lifestyle. This text will introduce current and future media industry professionals to the people, companies, and strategies that have proven to be real game changers by offering the marketplace a unique value proposition for the consumer.
Includes bibliographical references and indexes.
Description based on MARC record for print version.
Keywords: Mass media -- Management; Organizational effectiveness